Context-Dependent Phenotype of a Human Immunodeficiency Virus Type 1 Nucleocapsid Mutation - Cimarelli, Andrea (American Society for Microbiology, 2001)
The human immunodeficiency virus type 1 (HIV-1) nucleocapsid mutation R10A/K11A abolishes viral replication when present in proviral clone HIV-1(HXB-2), but it was found to have minimal effect on replication of the closely related HIV-1(NL4-3). Functional mapping demonstrated that a nonconservative amino acid change at nucleocapsid residue 24 (threonine in HIV-1(HXB-2), isoleucine in HIV-1(NL4-3)) is the major determinant of the different R10A/K11A phenotypes in these two proviruses. Threonine-isoleucine exchanges appear to modify the R10A/K11A phenotype via effects on virion RNA-packaging efficiency. The improved packaging seen with hydrophobic isoleucine is consistent with solution structures localizing this residue to a hydrophobic pocket that contacts guanosine bases in viral genomic RNA stem-loops critical for packaging.